2010
DOI: 10.1371/journal.pone.0012808
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogonial Stem Cell Niche and Spermatogonial Stem Cell Transplantation in Zebrafish

Abstract: BackgroundSpermatogonial stem cells (SSCs) are the foundation of spermatogenesis, and reside within a specific microenvironment in the testes called “niche” which regulates stem cell properties, such as, self-renewal, pluripotency, quiescence and their ability to differentiate.Methodology/Principal FindingsHere, we introduce zebrafish as a new model for the study of SSCs in vertebrates. Using 5′-bromo-2′-deoxyuridine (BrdU), we identified long term BrdU-retaining germ cells, type A undifferentiated spermatogon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
124
0
13

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(158 citation statements)
references
References 68 publications
(105 reference statements)
8
124
0
13
Order By: Relevance
“…Testis tissue from transgenic fish was digested with 0.2% collagenase and 0.12% dispase as described previously (Nó brega et al 2010). The resulting cell suspension was immediately submitted to fluorescence-activated cell sorting (FACS) using an in Flux cell sorter (BD Bioscience, San Jose, CA, USA, www.bdbiosciences.com).…”
Section: Expression Of Cyp17a1 and Cyp19a1 Genes In Sorted Testicularmentioning
confidence: 99%
See 1 more Smart Citation
“…Testis tissue from transgenic fish was digested with 0.2% collagenase and 0.12% dispase as described previously (Nó brega et al 2010). The resulting cell suspension was immediately submitted to fluorescence-activated cell sorting (FACS) using an in Flux cell sorter (BD Bioscience, San Jose, CA, USA, www.bdbiosciences.com).…”
Section: Expression Of Cyp17a1 and Cyp19a1 Genes In Sorted Testicularmentioning
confidence: 99%
“…Then, Egfppositive and -negative cells were collected into tubes, centrifuged in PBS (pH 7.4) for 10 min at 100 g and immediately submitted to RNA extraction using RNAqueous -Micro Kit (Ambion, Austin, TX, USA, http://www. ambion.com) as described earlier (Nó brega et al 2010). After cDNA synthesis, the threshold cycle (Ct) values of two endogenous reference genes (elongation factor 1-a, ef1a; 18S rRNA) and of the target genes were determined by qPCR.…”
Section: Expression Of Cyp17a1 and Cyp19a1 Genes In Sorted Testicularmentioning
confidence: 99%
“…However, this in vitro differentiation assay for premeiotic germ cells cannot exclude the possibility that mitotic spermatogonia were already affected by the defective somatic cells and lost competency to progress through meiosis before culturing. Further experiments, such as germ cell transplantations (Kawasaki et al, 2010;Nóbrega et al, 2010), should be performed to elucidate in which cell types these genes are required for normal progression of spermatogenesis.…”
Section: In Vitro Differentiation Assay For Premeiotic Germ Cells Usimentioning
confidence: 99%
“…They considered the mechanism of PGC migration to be highly conserved in fishes, and found that transplanting a single PGC was more efficient than transplanting blastomeres. Nobrega et al [107] transplanted spermatogonial stem cells of zebrafish into male and female recipients. From the results of donor-derived spermatogenesis and oogenesis, they demonstrated that germ cell differentiation could be influenced by the environment.…”
Section: Cell Engineering In Fish Reproductive Technologymentioning
confidence: 99%